First-principles study on the atomistic corrosion processes of iron - Chew, Khian Hooi; Kuwahara, Riichi; Ohno, Kaoru (Royal Society of Chemistry, 2018)
The corrosion of iron presents an important scientific problem and a serious economic issue. It is also one of the most important subjects in materials science because it is basically an electrochemical process and closely related to other topics such as the electrocatalysis of the oxygen reduction reaction. So far, many studies have been conducted to address the corrosion of iron, a very complicated process that occurs when iron is exposed to oxygen and water. An important question is, at which site of the iron surface the corrosion starts and how it results in the final stage of the corrosion. In the present study, as an example of superficial defects, Fe dimers sticking out of Fe(100) surfaces are considered in order to understand the iron corrosion process from first-principles using density functional theory. We found that the Fe dimers spontaneously react with O 2 and H 2 O to form Fe 2 (OH) 4 + 4OH - . Here, it is interesting to note that the Fe dimer plays the role of a water splitting catalyst, because the space above it is always vacant and can accept oxygen molecules many times for reacting with the surrounding water molecules. Then, if the Fe 2 (OH) 4 molecules are detached from the surface, they react with O 2 to form Fe 2 O(OH) 4 without an activation barrier, and, in turn, the Fe 2 O(OH) 4 and H 2 O molecules react to form Fe 2 (OH) 6 complexes with an activation energy of 0.653 eV. If these complexes further dissociate into Fe(OH) 3 molecules, they react with each other to form Fe 2 O 3 ·2H 2 O with an activation energy of 0.377 eV. This work may provide useful information on possible iron corrosion processes by water in the air.